Pain in polycystic ovary syndrome: a comprehensive bedside to bench perspective on an underrecognized symptom - Khodavirdilou, Lida; Wilkerson, Jenny L. (Frontiers in Pharmacology, 2026)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder, with a reported worldwide prevalence of 5%–20% in women of reproductive age. It is defined primarily by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. In addition to the reproductive and metabolic features of PCOS, patients often experience chronic pain, which is the most frequently reported symptom. Pain in the pelvic area, dysmenorrhea, bloating, and abdominal cramping are all common in PCOS patients. This paper reviews various factors that may influence pain in PCOS. Heightened inflammatory markers, such as interleukin-6, tumor necrosis factor alpha, and C-reactive protein may sensitize nociceptive pathways and promote an exaggerated immune response. Hyperinsulinemia and insulin resistance present in PCOS may further potentiate inflammatory processes. Alterations in sex hormones, specifically elevated androgens and a disproportionate estrogen to progesterone ratio, may alter nociceptive processing. Oxidative stress can potentiate sensitization through nociceptor hyperexcitability. We also discuss findings from animal models that mimic PCOS’s hormonal and behavioral aspects. Treatment modalities are reviewed, including hormonal therapies, insulin sensitizers, anti-androgens, lifestyle changes, as well as emerging therapies like agents that target the neuroimmune system and metabolic pathways. Overall, a deeper understanding of these interconnected mechanisms of this highly intertwined disorder is needed to help accurately diagnose it and improve the care of women experiencing PCOS-related pain.